Computational Analysis of Average Value and Amplitude in Magnetized Plasma Sheath (Swarnadwar, 2024)
For different obliqueness, ion velocity has been investigated numerically. Ions which are instreaming have to satisfy the criterion of Bohm-Chodura, to ensure the stability of plasma. Mean value as well as maximum/minimum amplitude is computed with different angles. Mean value of x-component is almost zero for all angles, whereas for y and z-component, mean value changes with different angles. On the other hand maximum amplitude almost changes for all angles. Ion velocity at presheath-sheath boundary, is affected by obliqueness of the field.